ENVIRONMENTAL MANAGEMENT, TYPES AND OBJECTIVES - Kurbanova Umida Sayetbekovna (Journals Park Publishing, 2022)
Environmental management is a component of the overall corporate governance system aimed at achieving the goals specified in the environmental policy. The following article is devoted to the study of environmental management and its main tasks and objectives.
Keywords: environmental management, ecology, environmental policy